2018
DOI: 10.1021/acs.inorgchem.8b00370
|View full text |Cite
|
Sign up to set email alerts
|

A Springloaded Metal-Ligand Mesocate Allows Access to Trapped Intermediates of Self-Assembly

Abstract: A strained, "springloaded" FeL iminopyridine mesocate shows highly variable reactivity upon postassembly reaction with competitive diamines. The strained assembly is reactive toward transimination in minutes at ambient temperature and allows observation of kinetically trapped intermediates in the self-assembly pathway. When diamines are used that can only form less favored cage products upon full equilibration, trapped ML fragments with pendant, "hanging" NH groups are selectively formed instead. Slight variat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 69 publications
1
10
0
Order By: Relevance
“…This generates two binding modes: convex (θ ≈ 90°) with nitrogen donors pointing away from the substituent(s), and concave (θ ≈ 40°) pointing in the same direction (Scheme S4). A similar backbone design was reported to lead to Fe-based helicates and tetrahedra, as well as knots and Borromean rings …”
mentioning
confidence: 74%
“…This generates two binding modes: convex (θ ≈ 90°) with nitrogen donors pointing away from the substituent(s), and concave (θ ≈ 40°) pointing in the same direction (Scheme S4). A similar backbone design was reported to lead to Fe-based helicates and tetrahedra, as well as knots and Borromean rings …”
mentioning
confidence: 74%
“…Our 'solution' did not actually end up being a solution, but it is an interesting idea: Can we use a metastable helicate such as the xanthone cage 10 as starting material? 63 Adding diamine ligands to 10 showed some extremely unusual selfassembly behavior. Depending on the nature of diamine, multiple different reaction outcomes could be observed that were independent of the nucleophilicity of the diamine and were instead completely dominated by the stability of the assembly.…”
Section: Syn Lettmentioning
confidence: 99%
“…The various outcomes are far too many to be described here, but the reader is directed to ref. 63 for a full account, with apologies for its length. One quick illustration of the large differences in reactivity between highly similar ligands is shown in Scheme 8.…”
Section: Syn Lettmentioning
confidence: 99%
See 1 more Smart Citation
“…Reports of the self-assembly of metallo-supramolecular structures under nonequilibrium conditions remain rare. 810…”
Section: Introductionmentioning
confidence: 99%